Dynamical Analysis of an Economic-Environment Model with Unilateral and Bilateral Control - Jing Xu; Mingzhan Huang; Jingen Yang (Mathematics)
Air pollution is one of the most important environmental problems in the world, it does harm to human health as well as hindering the sustainable development of the economy. The grim situation deserves wide attention and active participation in improvement. Thus, in this paper, considering the pollution control and sustainable development of the economy, we develop and investigate the economic-environment model with unilateral and bilateral control. To begin with, we briefly describe the dynamic behavior of the free system. It then follows the analysis of the system with unilateral and bilateral control. The existence of the order-1 and order-2 periodic solutions are investigated under different conditions. In addition, their stability is proven. The results show that the bilateral control strategy is beneficial to the sustainable development of economy.